1997
DOI: 10.1507/endocrj.44.23
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Study of the Pancreas Shows a Characteristic Lymphocytic Infiltration in Japanese Patients with IDDM.

Abstract: Abstract. We examined at autopsy 47 cases (22 males and 25 females) of insulin-dependent diabetes mellitus (IDDM) from 21 hospitals in Japan to clarify the pathological changes that occur in the pancreas vs. those in control patients. The mean age was 39.7 ± 13.9 (mean ± SD) years, and the duration of IDDM from clinical onset was 13.1 ± 6.5 years. Causes of death included renal complications, infections, acute diabetic complications such as ketoacidosis or hyper-or hypoglycemic coma, and atherosclerotic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 10 publications
3
25
0
1
Order By: Relevance
“…We identified 7 studies 10,11,27–31 encompassing 1272 subjects with DM who commented on the changes in exocrine pancreas (see Supplementary Table 1, http://links.lww.com/MPA/A487, for details on individual studies and summary of all studies in Supplementary Table 2, http://links.lww.com/MPA/A487). Four studies included controls 2730 ; however, only in 2 studies were findings in the exocrine pancreas compared between DM versus non-DM controls 28,29 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 7 studies 10,11,27–31 encompassing 1272 subjects with DM who commented on the changes in exocrine pancreas (see Supplementary Table 1, http://links.lww.com/MPA/A487, for details on individual studies and summary of all studies in Supplementary Table 2, http://links.lww.com/MPA/A487). Four studies included controls 2730 ; however, only in 2 studies were findings in the exocrine pancreas compared between DM versus non-DM controls 28,29 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 7 studies 10,11,27–31 encompassing 1272 subjects with DM who commented on the changes in exocrine pancreas (see Supplementary Table 1, http://links.lww.com/MPA/A487, for details on individual studies and summary of all studies in Supplementary Table 2, http://links.lww.com/MPA/A487). Four studies included controls 2730 ; however, only in 2 studies were findings in the exocrine pancreas compared between DM versus non-DM controls 28,29 (Table 2). Collectively in all 7 studies, 10,11,27–31 255 (59.4%) of 429 patients had pancreatic fibrosis, with all studies reporting greater than 50% prevalence of fibrosis in those with long-standing DM; Gepts 30 reported 18% prevalence of fibrosis in those with juvenile-onset DM dying less than 2 years of onset of disease.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to observation of rare insulitis and frequent lymphocytic infiltrate in the exocrine tissue in the pancreas from donors with T1D [43, 44], researchers from Osaka University Medical School recovered by pancreas tissue by biopsy from patients with newly diagnosed T1D and found detectable insulitis in approximately 50% of donors [45, 46]. The insulitis was composed of CD4 + and CD8 + T cells, B cells, and macrophages with noted HLA class I molecule hyperexpression in islets, intercellular adhesion molecule-1 (ICAM-1) expression on endothelial cells [47], and markers of an activated and pro-inflammatory environment were detected on infiltrating immune cells.…”
Section: Pancreatic Histology and Autoreactive T Cells In T1dmentioning
confidence: 99%
“…Although α-cells are plentiful in the islets of diabetic individuals and mice and rats, β-cells are reduced in numbers and secretion of insulin in response to nutrient signals is impaired. [90][91][92][93][94] Given these circumstances the question arises as to why β-cell mass and function is impaired in diabetes if α-cells are progenitors of β-cells? It seems that hyperplastic α-cells are poised to become β-cells but the environmental cues required to make this happen are missing.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…An extensive study of pancreases from 47 donors with type 1 diabetes showed over all a slight reduction in total α-cell mass per pancreas with some pancreases showing either no change or a marked increase in α-cell mass compared with non-diabetic, agematched controls. 91 In pancreases from type 2 diabetes donors α-cell mass appears to be maintained on average. 92 In another study islets composed nearly entirely of α-cells are described.…”
mentioning
confidence: 99%